2020
DOI: 10.3390/nano10091747
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Graphitic Carbon Nitride with Hydrogen Peroxide

Abstract: Graphitic carbon nitride (GCN) was synthetized by heating melamine and then it was thermally exfoliated for 1–3 h in air. Both bulk and exfoliated GCN nanomaterials were treated in the 10–30% aqueous solutions of H2O2 for us to study their modification. The light absorption properties were observed by the reddish color and the red-shifts of their UV-Vis spectra. The content of oxygen increased and hydrogen peroxide was supposed to partially oxidize C-OH groups to C=O ones and to form C-O-C groups instead of ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
1
2
1
Order By: Relevance
“…Thus, according to TGA-MS data, the control experiments and the FTIR results, a proposed structure of CN-K-OOH is displayed in Scheme 2 from both top and side view. It is suggested that the electrostatic attraction between K + and OOH À as well as the intermolecular hydrogen bond inside CN-K-OOH would cause the charge redistribution of CN-K-OOH to enhance its visible light absorption, which is different from the proposed O-doping mechanism in H 2 O 2 hydrothermal treatment of pristine CN, [15][16][17][18][19][20][21] and also different from the suggested cationdetermining mechanism in previous reports. 22,23 The present experimental results call for support from theoretical simulation work.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Thus, according to TGA-MS data, the control experiments and the FTIR results, a proposed structure of CN-K-OOH is displayed in Scheme 2 from both top and side view. It is suggested that the electrostatic attraction between K + and OOH À as well as the intermolecular hydrogen bond inside CN-K-OOH would cause the charge redistribution of CN-K-OOH to enhance its visible light absorption, which is different from the proposed O-doping mechanism in H 2 O 2 hydrothermal treatment of pristine CN, [15][16][17][18][19][20][21] and also different from the suggested cationdetermining mechanism in previous reports. 22,23 The present experimental results call for support from theoretical simulation work.…”
Section: Resultscontrasting
confidence: 74%
“…[12][13][14] In the case of Odoping, a H 2 O 2 hydrothermal treatment of pristine CN was usually carried out, where H 2 O 2 is used to generate oxygencontaining groups so as to modulate the electronic conguration of O-doped CN. [15][16][17][18][19][20][21] In 2019, Ge et al reported a simple H 2 O 2 treatment of Li-doped CN, and the obtained product shows a light absorption extending up to 650 nm. 22 However, Li atom doping into CN was suggested to be responsible for the optical property change.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TiO2exCl is mainly composed of the anatase phase, and it lacks long range crystallinity, as evidenced by the broad and low intensity reflections. The two main diffraction peaks for C3N4-TE at 13° and 27°, reported in Figure 1b, can be attributed to the (100) and (002) crystallographic planes of the material [27]. As reported in literature, the intensity of the main diffraction peak of C3N4 is very low when it is coupled with titania, due to the high crystallinity of P25 [28].…”
Section: Characterisation Of the Materialssupporting
confidence: 63%
“…[26]. C 3 N 4 is characterized by a graphitic 2D type structure [27] and, despite its moderate activity due to the high electron/hole recombination rate, the photocatalytic properties can be improved by chemical, mechanical, or thermal exfoliation, so the graphiticlike planes are exposed and functionalized [27]. Calcination is a successful methodology to obtain high surface area C 3 N 4 nanosheets (thermal exfoliation, TE).…”
Section: Introductionmentioning
confidence: 99%